Lymphokine-activated killer (LAK) therapy for advanced renal cell carcinoma clinical study on arterial LAK therapy and experimental study on LAK cell activity - Hayakawa, M (Hinyokika kiyo. Acta urologica Japonica, 1992)
Experimental and clinical studies were conducted on lymphokine-activated killer (LAK) cell therapy for advanced renal cell carcinoma (RCC). The traffic assay using radiolabeled LAK cells indicated short-term but appreciable accumulation of LAK cells in the tumor site when trans-arterially infused. By contrast, systemically infused LAK cells were localized not to the tumor tissue but to the lung. Therefore, we began treatment of the patients with extrapulmonary metastases by means of regional arterial administration of LAK cells and those who had pulmonary metastases by a systemic LAK therapy. Regimen of Interleukin-2 (IL-2) administration was bolus infusion of 5 x 10 U IL-2 twice daily. Frequency of LAK cell administration varied from one to three times a week depending upon the patient's condition. Eight out of 16 metastases, such as bone, muscle, and lymph node metastases, in 9 patients treated by arterial LAK therapy showed regression. Side effects during LAK therapy were not serious. Past history of having chemotherapy was an unfavorable factor that could reduce the sensitivity to LAK therapy. Our laboratory study showed the production of Interferon (IFN)-gamma and Tumor Necrosis Factor (TNF)-alpha by LAK cells when preincubated with RCC cells, which may indicate the mechanism of LAK cell-mediated antitumor activity in vivo. The study also showed that LAK cells as well as monocytes preincubated with the supernatant of LAK cells damaged normal endothelial cells in vitro, which suggested the possibility that LAK therapy risks increasing the frequency of brain metastasis by damaging the blood-brain barrier.(ABSTRACT TRUNCATED AT 250 WORDS)